WANITA: KEDUDUKAN DAN TINJAUAN KARIRNYA DALAM KEHIDUPAN SESUAI AL-QURAN DAN HADITS - Urwatul Wusqa (Universitas Islam Negeri Imam Bonjol Padang, 2011)
Women are the subject of endless, it is often said that Islam is very discriminatory against women but even if it compared with other religions, both divine religions such as Jewish and Christian; categorized as a religion or religions like Hindu religion Ardhi, will be found that real respect for women it is the religion of Islam. Similarly, if the comparison is made with the religion of nations before the coming of Islam it will be obvious that the symbolic gesture of respect for women, It is also recognized by people outside of Islam. About career women in the work will be seen also how moderate Islam in this case, but certainly not to leave its active role in the family with her husband in educating children and paying attention to them as the next generation in this life. Keywords : Women, career and IslamCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i2.77